Antarctic icebergs melt over the Southern Ocean: Climatology and impact on sea ice. (August 2016) - Merino, Nacho; Le Sommer, Julien; Durand, Gael; Jourdain, Nicolas C.; Madec, Gurvan; Mathiot, Pierre; Tournadre, Jean
Highlights: The Antarctic iceberg freshwater flux is estimated with a sea ice/ocean/iceberg model. Including vertical profiles of ocean currents improves modelled iceberg trajectories. The iceberg model overall reproduces the observed probability of iceberg presence. Iceberg meltwater increases sea ice formation with few local deviations. A climatology of iceberg freshwater flux is offered to be used in climate models Abstract: Recent increase in Antarctic freshwater release to the Southern Ocean is suggested to contribute to change in water masses and sea ice. However, climate models differ in their representation of the freshwater sources. Recent improvements in altimetry-based detection of small icebergs and in estimates of the mass loss of Antarctica may help better constrain the values of Antarctic freshwater releases. We propose a model-based seasonal climatology of iceberg melt over the Southern Ocean using state-of-the-art observed glaciological estimates of the Antarctic mass loss. An improved version of a Lagrangian iceberg model is coupled with a global, eddy-permitting ocean/sea ice model and compared to small icebergs observations. Iceberg melt increases sea ice cover, about 10% in annual mean sea ice volume, and decreases sea surface temperature over most of the Southern Ocean, but with distinctive regional patterns. Our results underline the importance of improving the representation of Antarctic freshwater sources. This can be achieved by forcing ocean/sea ice models with a climatological iceberg fresh-water flux.